2006
DOI: 10.1002/adic.200690002
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Determination of Isoflavonoids in Several Kudzu Samples by High‐Performance Capillary Electrophoresis (HPCE)

Abstract: Pueraria lobata is a rich source of isoflavonoids. The detection and identification of isoflavonoid components from root, stem, leaf, callus and cell samples, is very important for the best, safest and most efficacious use of kudzu as a medicinal plant, and for the studies on quantitative analysis in the secondary metabolism of isoflavonoids. In this paper, a simple, rapid and precise high-performance capillary electrophoresis (HPCE) method with diode array detection (DAD) has been developed for separation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…The Transcript of Pl4CL1 but Not Pl4CL2 Was Related to the Biosynthesis of Puerarin As previously reported, 35,36) the accumulation of puerarin was mostly detected in the roots compared to other organs (Fig. 5a).…”
Section: Biochemical Characterization Of Pl4cl1 and Pl4cl2supporting
confidence: 61%
“…The Transcript of Pl4CL1 but Not Pl4CL2 Was Related to the Biosynthesis of Puerarin As previously reported, 35,36) the accumulation of puerarin was mostly detected in the roots compared to other organs (Fig. 5a).…”
Section: Biochemical Characterization Of Pl4cl1 and Pl4cl2supporting
confidence: 61%
“…The results are shown in Table together with the amounts of puerarin and total isoflavones extracted under the optimised conditions. These extracted amounts were higher than those obtained in previous reports (Jiang et al ., ; Zhang et al ., ; Fang et al ., ; Cherdshewasart et al ., ; Lee and Lin, ; Du et al ., ), which further demonstrates that the response model adequately reflected the predicted optimisation.…”
Section: Resultsmentioning
confidence: 99%
“…This traditional Chinese medicine has been used for the treatment of various diseases and to promote bone healing for millenia and recent data suggest beneficial activity (16)(17)(18)(19)(20). The active ingredients have been identified as the isoflavones: puerarin, daidzin and daidzein, which have estrogenic activity (21)(22)(23)(24). Puerariae radix has shown positive therapeutic effects in animal studies (25)(26)(27) and in cell culture studies, Puerariae radix was shown to induce osteogenic activity (20,(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%